When in Rome! Complaint contagion effect in multi-actor service ecosystems - Chen, Ke; Chen, Jianxun; Wu, Zhan; Sharma, Piyush (Elsevier, 2020)
© 2020 Elsevier Inc. This paper explores the process by which other customers’ complaint behavior influences the focal customers’ complaint intentions in response to a service failure affecting multiple customers. The authors use social information processing theory to argue that the other customers’ complaint behavior has a positive effect on the focal customers’ complaint intentions, which they refer to as ‘complaint contagion effect’. Next, they posit mediating role of anger and moderating effects of social identification with other customers, perceived credibility of the other customers, and the focal customers’ prior relationship with the service provider in this process. Four experiments confirm the presence of complaint contagion effect and show that the complaint contagion effect is stronger for focal customers with high social identification with others, high perceived credibility of other customers and weak prior relationship of focal customers with the service providers.